Age is more than just a number! The role of age and maturity in the processes leading to early school leaving in Flanders (Belgium). (14th April 2018) - Van Praag, Lore; Van Caudenberg, Rut; Orozco, Mariana
Abstract : In many educational systems, age is used as a criterion to organise education. Children's age is used to group students together and indicate entry into particular programmes. The use of age for organisational purposes in education stems from the idea that age provides an indication of the development of children, which is associated with teaching and learning. However, more far‐reaching consequences of age‐related educational practices are insufficiently recognised in policy and academic research. Qualitative methods are used to study students and school personnel in diverse types of educational institutions in Flanders (Belgium) to assess how age and age‐related issues matter for the students' educational trajectories and educational decision‐making processes leading to early school leaving. Data analyses reveal that school staff members consider age and perceived maturity during evaluation procedures. Students also consider age during educational decision‐making processes: when getting older or being too old for the grade, students increasingly weigh the costs and benefits associated with getting an educational qualification and being enrolled in school and alternative opportunities. Students' expectations related to age shape their school experiences and feelings of belonging. The findings of this study demonstrate how these educational practices add to the reproduction of inequalities through education. These results could inform debates concerning the evaluation procedures in secondary education, compulsory education and the reduction of early school leaving in Europe.